Clinical and morphological case of developing liver cirrhosis associated with viral hepatitis in a young patient - O. V. Vorobeva (Sankt-Peterburg : NIIÈM imeni Pastera, 2021)
The significance of chronic hepatitis is determined not only by the disease per se, but also by the increased risk of the formation of long-term adverse effects such as liver cirrhosis. Viral cirrhosis of the liver (as the outcome of chronic hepatitis B, C, B + D) comprise from 10% to 24.5% of all liver cirrhosis cases. Cirrhosis of the liver is considered as an irreversible stage of chronic hepatitis, more often observed in men above 40 years, but recently more and more its cases are found in young, working ones leading to disability. Due to the high liver regenerative potential, a prognosis for liver lesions of different etiologies may be rather favorable. As a result, early diagnostics, dynamic monitoring and the use of promising methods for treating liver pathology to stimulate its regeneration that compensates for lost liver functions are necessary. In the clinical and morphological case, pathomorphological changes in organs with liver cirrhosis, which developed as a result of viral hepatitis are described. The aim of the study was to describe pathomorphological changes in organs during liver cirrhosis, which developed due to viral hepatitis, which led to multiple organ failure in a young patient. Materials and methods. The analysis of the obtained accompanying medical documentation (outpatient card, medical history) was performed. The standard methodology of autopsy was used. To process histological sections of autopsy material, hematoxylin-eosin staining was used. Results. Histological examination in the liver shows development of portal tract fibrosis with lymphohistio cytic infiltration, formation of monolobular regenerated nodes, signs of edema, areas of demyelination, dystrophic changes in neurocytes, signs of acute renal failure, a combined profound change in the kidneys detected in the lungs and brain, which resulted in multiple organ failure and subsequent lethal outcome in a young patient. The early formation of portal hypertension with liver cirrhosis, esophageal and gastric varicose veins dilatation lead to fatal bleeding in half of patients. Therefore, timely diagnosed cirrhosis and hepatitis as their predecessors is one of the most relevant issues in medicine.